Retinal Bionic Eye Development: Pengembangan Mata Bionik Retina - Ahmed, Nooralhuda Abbood (Procedia of Engineering and Life Science, 2025)
The retinal bionic eye, also known as a retinal prosthesis, is a groundbreaking biomedical technology designed to restore vision in individuals with severe retinal degenerative diseases, such as retinitis pigmentosa (RP) and age-related macular degeneration (AMD). These conditions lead to the loss of photoreceptor cells in the retina, impairing the ability to perceive visual information. Retinal bionic eyes work by bypassing damaged photoreceptors and directly stimulating the remaining functional retinal neurons through an implanted electrode array. This technology typically consists of a camera system that captures visual information from the environment, a processing unit that converts the image into electrical signals, and an electrode array that delivers these signals to the retina. The processed signals are then transmitted to the brain through the remaining retinal neurons. The goal is not to restore normal vision but to provide users with the ability to detect light, recognize shapes, and perceive motion, ultimately improving their independence and quality of life. Retinal bionic eyes have shown significant promise in clinical trials and have been approved for use in select patients, offering a new sense of hope for those who have experienced vision loss. Although the technology is still evolving, current devices are providing basic visual functions that help patients navigate their environments, and ongoing research aims to improve resolution, enhance visual acuity, and create devices that offer more natural sight. Future developments in neuroprosthetics, artificial intelligence, and biocompatible materials hold the potential to further enhance the effectiveness of these systems, making retinal bionic eyes an important tool in the fight against irreversible blindness